2019
DOI: 10.1111/jocs.14316
|View full text |Cite
|
Sign up to set email alerts
|

Late management of the aortic root after repair of tetralogy of Fallot: A European multicentre study

Abstract: Objectives: We sought to determine the indications, type, and outcomes of reoperations on the aortic root after repair of tetralogy of Fallot (TOF). Methods: Eleven centers belonging to the European Congenital Heart SurgeonsAssociation contributed to the data collection process. We included 36 patients who underwent surgical procedures on the aortic root, including surgery on the aortic valve and ascending aorta, between January 1975 and December 2017. Original diagnoses included TOF-pulmonary stenosis (n = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Recent follow-up data in tetralogy of Fallot patients have identified that 29% of patients require aortic reoperations for: aortic insufficiency (53%), aortic insufficiency and ascending aortic dilation (28%), aortic root dilation (11%), and isolated ascending aortic dilation (8%). 22 The presented cohort of patients demonstrated increased ascending aortic stiffness despite normal aortic size, suggesting that elevated stiffness results from abnormal flow patterning and resultant nonuniform flowmediated shear forces. Although the present study demonstrates 2-dimensional PC-MRI data, our group has also demonstrated that supra-physiologic helical flow patterns exist in the ascending aorta of patients after tetralogy of Fallot repair by 4-dimensional flow MRI and have demonstrated an association with abnormal systolic outflow patterns within the left ventricle.…”
Section: Commentmentioning
confidence: 83%
“…Recent follow-up data in tetralogy of Fallot patients have identified that 29% of patients require aortic reoperations for: aortic insufficiency (53%), aortic insufficiency and ascending aortic dilation (28%), aortic root dilation (11%), and isolated ascending aortic dilation (8%). 22 The presented cohort of patients demonstrated increased ascending aortic stiffness despite normal aortic size, suggesting that elevated stiffness results from abnormal flow patterning and resultant nonuniform flowmediated shear forces. Although the present study demonstrates 2-dimensional PC-MRI data, our group has also demonstrated that supra-physiologic helical flow patterns exist in the ascending aorta of patients after tetralogy of Fallot repair by 4-dimensional flow MRI and have demonstrated an association with abnormal systolic outflow patterns within the left ventricle.…”
Section: Commentmentioning
confidence: 83%
“…Commonly, surgical intervention is the primary option when the diagnosis of aortic complications after rTOF is confirmed. Whereas the risks for both postoperative complications and early mortality are significantly higher, therefore, preoperative assessment should be emphasized ( 11 ). Currently, the recommended threshold of ascending aorta for surgical intervention is set as 55 mm ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was no early or late mortality after aortic surgical reintervention in our patients. However, a multicenter retrospective study that investigated the outcomes of late surgical management of aortopathy in 36 patients with rTOF reported high risk of early (14%) and late (16%) operative mortality, which was associated with larger aortic diameters [6]. This emphasizes the importance of addressing aortopathy during the planning of any future surgical reintervention, especially with PVR, which represents about one-third of re-interventions and was correlated with proximal aortic dilatation.…”
Section: Surgical Reinterventionsmentioning
confidence: 99%
“…Some of these factors include the rate of progression of aortic dilatation; the severity of AR; the number of prior cardiac surgical procedures, which may increase the risk of further surgery; and the presence of family history of TAD or genetic mutation, which can accelerate the rate of aortic dilatation and dissection. Some studies have shown that both emergent [5] and elective [6] proximal aortic and/or aortic valve surgeries in patients with rTOF carry a high risk of operative mortality. Hence, addressing proximal aortic dilatation and AR in the same session as PVR may be logical.…”
Section: Surgical Reinterventionsmentioning
confidence: 99%
See 1 more Smart Citation